Новый и малоизученный виды рода Neoschoengastia Ewing, 1929 (Acariformes, Trombiculidae) с Украины - Гуща, Г.И. (Вестник зоологии, 1981)
The paper presents a description of Neoschoengastia (Hypogastia) simonovichi sp. n. and a redescription of Neoschoengastia (Neoschoengastia) lucida Schluger Belskaja, 1972 with the differential diagnosis of closely related species. The larvae wer‹ collected from birds in south regions ofthe Ukraine.